Sertoli cells for cell transplantation: pre‐clinical studies and future perspectives. (30th March 2018) - Luca, G.; Arato, I.; Sorci, G.; Cameron, D. F.; Hansen, B. C.; Baroni, T.; Donato, R.; White, D. G. J.; Calafiore, R.
Summary: Sertoli cells are located in the testes where they control several key functions in spermatogenesis. Over the past 30 years, Sertoli cells have been upgraded from a simple scaffold‐like structural system to a dynamic functional system of intercellular support that delivers potent immunomodulatory and trophic factors. Since the discovery of new Sertoli cell secretory products, these cells have been utilized in experimental cell transplantation and co‐transplantation protocols aimed at treating both chronic inflammatory and degenerative disorders. For these reasons, this work reviews the application of both naked and microencapsulated Sertoli cells used in cell transplantation studies of several chronic or autoimmune diseases such as diabetes mellitus, Laron dwarfism, and Duchenne muscular dystrophy and in studies aimed at the prevention of skin allograft rejection.